2019
DOI: 10.2106/jbjs.19.00648
|View full text |Cite
|
Sign up to set email alerts
|

The Propeller Flap for Traumatic Distal Lower-Limb Reconstruction

Abstract: Background: Defects in the distal third of the leg are difficult to cover and often require free tissue transfer, even for defects of limited sizes. Propeller flaps have been designed specifically as an alternative to free tissue transfer but at times have been associated with unacceptably high complication rates. We therefore aimed to prospectively assess our own institutional experience with this technique and to define its role in lower-limb reconstruction. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Lese et al, [43] in their study showed a mean healing-time of 5.9 weeks (range, 2 to 32 weeks). Demiri et al, [50] in their retrospective comparative study between Reverse neuro-cutaneous (Reverse Sural and Lateral Supramalleolar) versus Perforator Propeller flaps for reconstruction of diabetic wounds at foot and ankle, had a mean healing-time of 48.1 (6.9 weeks) for neurocutaneous and 40.7 (5.8 weeks) days for Perforator Propeller flaps.…”
Section: Iii-healing Timementioning
confidence: 85%
See 2 more Smart Citations
“…Lese et al, [43] in their study showed a mean healing-time of 5.9 weeks (range, 2 to 32 weeks). Demiri et al, [50] in their retrospective comparative study between Reverse neuro-cutaneous (Reverse Sural and Lateral Supramalleolar) versus Perforator Propeller flaps for reconstruction of diabetic wounds at foot and ankle, had a mean healing-time of 48.1 (6.9 weeks) for neurocutaneous and 40.7 (5.8 weeks) days for Perforator Propeller flaps.…”
Section: Iii-healing Timementioning
confidence: 85%
“…In Moullot et al, [30] study, the mean hospital stay for free flaps was 24 days. According to Lese et al, [43] the mean hospital stay for Perforator Propeller flaps was 11.2±3.6 days (range from 7 to 23), with patients who had post-operative complications requiring more weeks until complete healing and staying in the hospital longer. Freestyle Perforator-Plus of Yoon et al, [39] for pressure sore reconstruction, had a mean hospital-stay of 20.1±2.62 SD days (range: 18-26 days) in comparison to perforator-based island flaps mean 22.9± 5.25 SD days (range: 18-35 days).…”
Section: Ii-hospitalization Timementioning
confidence: 98%
See 1 more Smart Citation
“…(5) the area involved (anteromedial, anterolateral, posterolateral, posteromedial, or a combination thereof); (6) type of flap coverage; or (7) complications (partial necrosis, complete necrosis, incidence of infection, and any other complication).…”
Section: Methodsmentioning
confidence: 99%
“…However, a recent study was able to correlate a higher rate of propeller flap problems with an increased number of comorbidities in patients undergoing lower limb reconstruction. 26 It seems clear that heavy smoking, diabetes, and peripheral vascular disease are some of the important issues associated with flap healing problems. 6,23,24 Dealing with the Perforator: How to Avoid Venous Congestion…”
Section: Experience With the Propeller Flapmentioning
confidence: 99%